Action Learning Strategy to Enhance Students Speaking Skill: A Classroom Action Research - Putra, Rangga Mega; Solekhah, Siti; Agustina, Diyah Dwi; Sobirov, Bobur (Anglophile Journal, 2021)
The aim of this study was improve the students’ English speaking skill through action learning strategy at 9 of SMP Islam Assya’roniyyah. The method used Classroom Action Research (CAR) that developed by Kemmis and Mc Taggart (2013). It consists of four steps namely, planning, acting, observing, and reflecting. Improvement the problem in this research was brought by the series of cycle. The procedures of research were performs by administrating two cycles. Each cycle contain four steps which are planning, action, observation, and reflection. The collecting data used test, observation, and interview. Analyzing data used the mean each post-test in cycle. The result showed that the students’ speaking skill improved. It can be noticed that there was an improvement in every cycle from the students’ behavior and achievement. Action learning strategies facilitate the students to speak in way, they reduce students’ anxiety so they can speak freely without being afraid to make a mistake, they increase the students’ motivation in learning speaking, and the most important the students do not think that English is a difficult subject. Keywords: Action Learning Strategy, English Speaking Skill, Classroom Action Research